First record of Pherbellia shatalkini Rozkošný (Diptera: Sciomyzidae) from Mongolia, with a redescription of the male genitalia - Kurina, Olavi; Knutson, Lloyd (Zootaxa, 2019)
Following examination of type material of Pherbellia shatalkini Rozkošný, two specimens of snail-killing flies (Sciomyzidae) from Mongolia that initially had been determined as an undescribed species were confirmed as P. shatalkini, the first documentation of this species from Mongolia. The male genitalia are illustrated and redescribed in great detail.